NUEVOS LIMITES PARA LA DISTRIBUCION DE SALIX HUMBOLDTIANA WILLD., SALICACEAE, EN CHILE NEW DISTRIBUTION RANGE LIMITS OF SALIX HUMBOLDTIANA WILLD., SALICACEAE, IN CHILE - Enrique Hauenstein (Universidad de Concepción, 2005)
Salix humboldtiana Willd. is reported for the first time from wetlands in the Araucanian Region of Chile. Furthermore, our inspection of existing herbarium collections shows that the range limits previously reported in the literature considerably underestimate the range of this species in Chile. These findings therefore represent an extension of the southern range limit of S. humboldtiana by ca. 2º of latitude (from 36º59' to 38º47'S), and an extension of the northern limit in Chile by more than 9º of latitude (27º21' to 18º35'S)